PETROMAGNETIC STUDY ON LAVA FROM MOUNT BLAU AND YOUNG IJEN IN THE IJEN VOLCANIC COMPLEX, BANYUWANGI, EAST JAVA - HADIYAT - NIM: 12314004, HANDAYANI
Characterization of volcanic rocks is very useful in understanding the process of magmatism in volcanic areas. In this study, the lava characterization of the Ijen Volcanic Complex was carried out because it has a unique attraction. In contrast to previous studies, measurements of rock magnetic susceptibility as magnetic parameters was applied and can be used as a sensitive indicator of certain geological processes. Rock characterization is also accompanied by identification of petrogenesis (origin of rocks) using petrographic and geochemical methods. The three methods were applied to Blau lava samples (BLA, BLB and BLC) and Young Ijen (IL3B, IL3E, IL3F, IL3H, IL3J, and IL3K) which are the oldest and youngest eruption centers in the caldera of the Ijen Volcanic Complex. In addition to characterization, this research is aimed at identifying magmatism processes that affect the magnetic characteristics of rock samples. The results showed that all Blau lava samples were andesite from the calc-alkaline high-K magma series. In addition to the chemical composition, all samples also have uniform hypocrystalline porphyritic textures so that they are thought to be the same product of magma differentiation through crystal fractionation. The value of magnetic susceptibility (χLF) of all samples was relatively close around 1682,921848,84 (1ÃƒÂ—10-8m3/kg). While the Ijen Muda lava sample has a hypocrystalline porphyritic texture, chemical composition and varying magnetic susceptibility values. IL3E, IL3F and IL3J samples are basaltic andesite with a value of χLF 842.41342.68 (1ÃƒÂ— 10-8 m3/kg) although IL3B, IL3H and IL3K were andesite with a value of χLF 1382.36-1878.56 (1ÃƒÂ—10-8 m3/kg). The Young ljen lava sample comes from magma mixing calc-alkaline high-K magma series and calc-alkaline K-medium that undergoes crystal faxing. The texture of the six Ijen Muda lava samples is relatively diverse, possibly due to the time of crystal fractionation delay when experiencing surface transport. Crystal fractionation causes differences in the composition of SiO2 and the abundance of magnetic minerals. The magmatism process affects the abundance of magnetic minerals as the main factor influencing the value of magnetic susceptibility in Young Ijen lava samples.